Outcomes in patients with acute kidney injury reviewed by Critical Care Outreach: What is the role of the National Early Warning Score?. (November 2017) - Potter, Daniel A; Wroe, Nicholas; Redhead, Helen; Lewington, Andrew JP
Introduction: This study investigated outcomes in critically unwell acute kidney injury patients and the role of the National Early Warning Score and other factors in identifying patients who experience negative outcomes. Methods: Retrospective cohort study investigating 64 patients seen by Critical Care Outreach between November 2014 and February 2015. Mortality at one year was analysed using multivariate regression; all other statistical tests were non-parametric. Results: Forty-four per cent of patients required escalation to higher level care, 56% failed to survive beyond one year and 30% of those who did survive had a deterioration in renal function. Previous acute kidney injury significantly predicted mortality but the National Early Warning Score did not. A subgroup of patients developed Stage 3 acute kidney injury before a rise in National Early Warning Score. Conclusions: Acute kidney injury in the Critical Care Outreach patient population is associated with high morbidity and mortality. Previous acute kidney injury and acute kidney injury stage may be superior to the National Early Warning Score at identifying patients in need of Critical Care Outreach review.